Editors-in-chief in social sciences: Mapping the institutional, geographical, and gender representation between academic fields - Manuel Goyanes; Luis de-Marcos; Timilehin Durotoye; Triwik Kurniasari; Homero Gil de Zúñiga (PLoS ONE, 2025)
This study systematically maps the network structure of the editors-in-chief in social sciences journals, focusing on their gender representation, geographical distribution, and institutional composition. Drawing upon large-scale data from 3,320 JCR-ranked journals of 57 different fields in the social sciences (4,868 editors-in-chief from 1,485 affiliations of 71 countries), the study aims to illustrate the current connections of editorial leadership in social sciences. Findings reveal that two countries—the U.S. and the U.K.—and their institutions shape almost all fields of the social sciences, with institutions from other geographies, particularly non-English-speaking countries, being substantially underrepresented. However, there is no central institution that dominates across all fields, but within dominant geographies, a reduced number of different affiliations prevail in the most important intellectual terrains. In terms of gender representation, there is a significant imbalance across all dimensions under study. Male editors-in-chief outnumber females across most fields (66.67%), countries (76.60%), and affiliations (63.16%). All in all, by critically mapping the connections of editors-in-chief in social sciences journals, this study seeks to advance our understanding of the current structure of editorial governance and, in turn, stimulate initiatives aimed at fostering a more representative leadership in social science, keeping levels of scientific excellence constant.